Evaluasi Pengalaman Pengguna pada Aplikasi E-Commerce Tapp Market Menggunakan Parameter UX Honeycomb - Priska Suseta; Retno Indah Rokhmawati; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Tapp Market is a location-based e-commerce mobile application that provides online purchases with cash easily and reliably. As of January 10th, 2019, Tapp Market e-commerce mobile application has been downloaded 50,000 times and received 2,000 reviews. However, Tapp Market e-commerce mobile application only gets a total rating 3.2 out of 5.0. The purpose of this research is to map the problems from every aspect offered, each contributing to improvements. UX Honeycomb is used as a parameter to measure user experience from Tapp Market e-commerce mobile application. Aspects which measured in this research are credible, valuable, useful, and usable. The number of samples used are 60 respondents. As requirement, respondents are users who have used or new to using Tapp Market e-commerce mobile application. The data collection method used is questionnaire transferred in the form of online and offline. The data obtained consisted of quantitative and qualitative data (triangulation). Data analysis was performed using simple descriptive statistical formula to find the average value and standard deviation. The results of the analysis show the percentage score average from credible aspect is 64.45% with good category, the percentage score average from valuable aspect is 69.27% ​​with good category, the percentage score average from useful aspect is 77.19% with good category, and percentage score average from usable aspect is 64.93% with good category. Based on the Mobile Principles of the Retail Application and Site, recommendations are given in the form of improvements to each indicator. Indicators that need to be improved on credible aspect are indicators with codes CR1, CR2, CR3, and CR4. Indicators that need to be improved on valuable aspect are indicators with codes VL1, VL2, and VL4. Indicators that need to be improved on useful aspect are indicators with codes UE1 and UE3. Indicators that need to be improved on usable aspect are indicators with codes UA2, UA4, and UA6.